The beta adrenergic receptor antagonist propranolol alters mitogenic and apoptotic signaling in late stage breast cancer - Alexa Montoya; Armando Varela-Ramirez; Erin Dickerson; Eddy Pasquier; Alireza Torabi; Renato Aguilera; Zeina Nahleh; Brad Bryan (Biomedical Journal, 2019)
Background: Substantial evidence supports the use of inexpensive β-AR antagonists (beta blockers) against a variety of cancers, and the β-AR antagonist propranolol was recently approved by the European Medicines Agency for the treatment of soft tissue sarcomas. Prospective and retrospective data published by our group and others suggest that non-selective β-AR antagonists are effective at reducing proliferative rates in breast cancers, however the mechanism by which this occurs is largely unknown. Methods: In this study, we measured changes in tumor proliferation and apoptosis in a late stage breast cancer patient treated with neoadjuvant propranolol. We expounded upon these clinical findings by employing an in vitro breast cancer model, where we used cell-based assays to evaluate propranolol-mediated molecular alterations related to cell proliferation and apoptosis. Results: Neoadjuvant propranolol decreased expression of the pro-proliferative Ki-67 and pro-survival Bcl-2 markers, and increased pro-apoptotic p53 expression in a patient with stage III breast cancer. Molecular analysis revealed that β-AR antagonism disrupted cell cycle progression and steady state levels of cyclins. Furthermore, propranolol treatment of breast cancer cells increased p53 levels, enhanced caspase cleavage, and induced apoptosis. Conclusion: Collectively, these data provide support for the incorporation of β-AR antagonists into the clinical management of breast cancer, and elucidate a partial molecular mechanism explaining the efficacy of β-AR antagonists against this disease. Keywords: Breast cancer, Propranolol, Beta blockade, Beta adrenergic receptor, Proliferation, Apoptosis